Osteology of the feeding apparatus of Magnificent Frigatebird Fregata magnificens and Brown Booby Sula leucogaster (Aves: Suliformes) - Carlos, Caio José; Alvarenga, Jéssica Guimarães; Mazzochi, Mariana Scain (Papéis Avulsos de Zoologia, 2017)
In this paper, we describe the skulls of Magnificent Frigatebird Fregata magnificens (Fregatidae) and Brown Booby (Sulidae) Sula leucogaster, with focus on the structures associated with the Musculi mandibulae. We discuss the results in the context of the feeding biology of the two species, which feed mainly on flying fish and squids. Frigatebirds capture prey from just above, or just below, the water surface in flight. The hook-shaped Apex maxillae in F. magnificens can be viewed as an adaptation for grasping prey from near the water surface. Boobies catch prey by plunging; thus, the dorsoventrally flattened skull and conical bill of S. leucogaster may reduce water resistance when it dives, or swims underwater. The bill is long in both species, such that it is on average 70% of the whole skull length in F. magnificens and 60% in S. leucogaster. Consequently, the Mm. mandibulae in the two species are more posteriorly positioned relative to the Apex rostri. This results in low mechanical advantage for the mandible opening-closing lever, indicating adaptations for a fast, rather than a strong, bite. Fast-moving mandibles would be advantageous for ‘mandibulating’ prey while swallowing. The Fossa musculorum temporalium and the Palatum osseum in both species provide a broad area for origins of the Musculus adductor mandibulae externus (all parts) and the Musculus pterygoideus. The Processus orbitalis quadrati is longer and thicker in F. magnificens than in S. leucogaster, and so is the Musculus pseudotemporalis profundus. We suggest that Mm. adductores mandibulae are relatively well developed in the two species; therefore, their mandibulae are still probably capable of a powerful adduction. In both species there is a mechanisms that contribute to protect the jaws from disarticulation and damage. Such mechanism involves the incorporation of a ‘flange-like’ Crista intercotylare on the Margo medialis cotylae medialis fossae articularis quadratica that grips the Condylus medialis quadrati. In S. leucogaster, the retractor-stop ‘notch’ formed by Ossa lacrimale et nasale also serves to protect the jaws against sudden external forces when birds are diving or swimming underwater for prey. A more detailed hypothesis for the jaw movements and strength in F. magnificens and in S. leucogaster and their relation with feeding habits should necessarily incorporate data on the jaw and anterior neck musculatures.